2022
DOI: 10.21203/rs.3.rs-1451157/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deficit Financing Components, Inflation and Capital Formation in Nigeria: Evidence from A Direct and Indirect Analysis

Abstract: Deficit financing occasioned by low domestic savings and low capital formation, have characterised the Nigerian economy since the 1970s with attendant increase in inflation. Empirical studies on Nigeria have shown that deficit financing directly affects inflation and capital formation when examined independently. However, little attention has been paid to a simultaneous investigation of the direct and indirect effects of deficit financing components on inflation and capital formation in Nigeria. Consequently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…As the nominal exchange rate rises, the country's exports become cheaper in the international market. Although Nigeria operated a xed exchange rate regime till mid-1986, the perceptions about the country's export as being too expensive have seen the domestic currency (naira) undergo several liberalisation policies to date (Aladejare, 2022b). Subjecting the naira to the operations of market forces is expected to aid export demands, improve foreign earnings, and enhance the country's long-term productivity.…”
Section: Dynamic Ardl Simulationsmentioning
confidence: 99%
“…As the nominal exchange rate rises, the country's exports become cheaper in the international market. Although Nigeria operated a xed exchange rate regime till mid-1986, the perceptions about the country's export as being too expensive have seen the domestic currency (naira) undergo several liberalisation policies to date (Aladejare, 2022b). Subjecting the naira to the operations of market forces is expected to aid export demands, improve foreign earnings, and enhance the country's long-term productivity.…”
Section: Dynamic Ardl Simulationsmentioning
confidence: 99%
“…As the nominal exchange rate rises, the country's exports become cheaper in the international market. Although Nigeria operated a fixed exchange rate regime till mid-1986, the perceptions about the country's export as being too expensive have seen the domestic currency (naira) undergo several liberalisation policies to date (Aladejare, 2022b). Subjecting the naira to the operations of market forces is expected to aid export demands, improve foreign earnings, and enhance the country's long-term productivity.…”
Section: Dynamic Ardl Simulationsmentioning
confidence: 99%
“…This outcome implies that the supplementary funds derived through deficit financing to augment the use of revenue for infrastructural development have been income-diminishing. Extant studies such as Ebi and Aladejare (2022) and Aladejare (2022b) have observed that annually, an enormous share of Nigeria's deficit financing funds are often expended on import demands and subsidy payments. Such measures cannot promote a country's income growth and overall economic wealth.…”
Section: Dynamic Ardl Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing policy synergy between a country's monetary and scal authorities can accelerate or decelerate external debt. For instance, the scal authorities in developing countries often justify their need for borrowing on employment creation, economic growth, and infrastructure development needs (Aladejare, 2022b).…”
Section: Introductionmentioning
confidence: 99%